From Historical Memory to Cultural Identity: The Construction of Archetypal Symbols for the Statues and Images of Mazu - Zhang, Beibei (Religions, 2024)
The archetypal symbols of Mazu’s statues and pictorial art are the mapping of a religious concept, a way of belief, and some programmed behaviours and rituals. They are also emotional imagery used to arouse the cultural awareness of international Chinese, inspire them to help and trust each other, to encourage and to comfort each other, to share weal and woe, and to always forge ahead. From the perspectives of historical memory, visual signs, and cultural identity, this paper explores the construction of archetypal symbols for the statues and images of Mazu. In addition, this paper generalizes the foundation and methods of this construction by analyzing the artistic forms and characteristics of the surviving Mazu images and statues and comparing the rules and regulations for making statues of other religions. Moreover, we consider the function of artistic signs that refer to and symbolize broader religious concepts and beliefs. The purpose of this work is to make the image of Mazu more visually present and strengthen cultural identity.